ANALISIS PERATURAN PENGEMBALIAN BARANG BUKTI YANG TIDAK SESUAI DENGAN KEADAAN AWAL WAKTU PENYITAAN - Susilo, Agung Hendro; astuti, pudji (Universitas Negeri Surabaya, 2021)
Abstract Handling of confiscated evidence is guided by the law number 8 of 1981 concerning the criminal procedure code and the regulation of the minister of environment and forestry number. P.26/Menlhk/Setjen/Kum.1/4/2017 concerning the handling of evidence of environmental and forestry crime. The two rules do not mention